2014
DOI: 10.1088/1367-2630/16/12/123011
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide density distributions in the effluent of an RF argon APPJ: effect of gas flow rate and substrate

Abstract: The effluent of an RF argon atmospheric pressure plasma jet, the so-called kinpen, is investigated with focus on the nitric-oxide (NO) distribution for laminar and turbulent flow regimes. An additional dry air gas curtain is applied around the plasma effluent to prevent interaction with the ambient humid air. By means of laser-induced fluorescence (LIF) the absolute spatially resolved NO density is measured as well as the rotational temperature and the air concentration. While in the laminar case, the transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 49 publications
(80 reference statements)
3
56
0
Order By: Relevance
“…At a gas flow rate of 3 slm and a corresponding Reynolds number of ≈ Re 3000 the flow is expected to be fully turbulent. The computed ambient species densities agree well with mass spectrometric measurements [38][39][40].…”
Section: Model Descriptionsupporting
confidence: 71%
“…At a gas flow rate of 3 slm and a corresponding Reynolds number of ≈ Re 3000 the flow is expected to be fully turbulent. The computed ambient species densities agree well with mass spectrometric measurements [38][39][40].…”
Section: Model Descriptionsupporting
confidence: 71%
“…For the kINPen plasma jet, this includes for example nitrite, nitrate, hydrogen peroxide, superoxide, hydroxyl radical, peroxynitrite, and singlet oxygen [72][73][74]. Plasma gas phase analysis suggests the presence of many others [75][76][77]. Yet, if organic target molecules and/or cells are not present at the site of species creation or deposition, short- lived species yield more stable products such as hydrogen peroxide or hypochlorous acid [73].…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] It is a streamerlike propagation that produces reactive species while it propagates in an ambient air. [16][17][18][19][20][21][22][23][24] For instance, although it is known that the discharge polarity affects the shape, length, and emission profile of the plasma jet, 25 few studies have reported its effect on the reactive species production. 14,15 Although many studies have measured reactive species in the plasma jet, a lot of things are still ambiguous about the relation between the plasma bullet propagation and the production of reactive species.…”
Section: Introductionmentioning
confidence: 99%